Pemberian infusum Benalu Duku (Loranthaceae daendropthoe spesies) aman bagi fungsi dan jaringan ginjal tikus - Mustika, Arifa (Pokja Herbal Medicine FK UGM, 2008)
Loranthaceae daendropthoe is a herbal preparation which has been shown as cell antiproliferant and traditionally used as anticancer. The infusion of the plant is given via oral route. which is subsequently absorbed by gastrointestinal and excreted inkidneyr.This study examined whether Loranthaceae daendropthoe makes kidney tissue damage in animal model. Mouse as animal models were divided into two groups. The control group was given with aquademineralisata and treatment group was given with infusion of Loranthaceae daendroprhoe. Serum nitrogen and creatinin. specific marker of kidney necrosis and the histology of mouse liver were studied l7 days after the treatment with plant infusion. Data of serum Serum nitrogen and creatinin and histology were compared between treatment and control groups. The result suggested that the inclusion of-Loranthaceae daendropthoe did not cause kidney damage